Plato and Antisthenes in the Phaedo: A Reflexive Reading. Part One - Mazzara, Giuseppe (Peitho. Examina Antiqua, 2019)
The purpose of this study is not so much to show the presence of Antisthenes in the dialogue, but rather to examine what Plato alludes to. The controversy over ideas between the two Socratics is historically very well-attested, as can already be seen in the Cratylus. Thus, it is reasonable to assume that this controversy must have affected Plato when he was writing a dialogue in which the importance of ideas and his new logic is undeniable. Hence, this paper will investigate the following question: what impact could Antisthenes’ denominative and definitory logic have on the equally denominative and definitory logic presented in the Phaedo given that the latter work in all probability preceded the Sathōn? In light of what is said in the dialogue, the answer focuses primarily on what would not be said. Thus, this study has been divided into two parts: Part one shows how the so-called “second navigation” emerges as an objection to the insufficiency of the responses given by the physiologists. Tellingly, certain “common opinions” are regarded as perplexing and individuals holding them are referred to with the indeterminate tis, which – as is argued – must have included Antisthenes. Indeed, Tht. 108c7–8 reports the latter to have made common opinions a cornerstone of his denominative logic. Part two, on the other hand, is devoted to examining the so-called “final argument.” Here, Antisthenes’ presence seems somewhat more nuanced given his incomplete knowledge of the new logic of irreversible opposites which was worked out by Plato for the purpose of demonstrating the immortality and indestructibility of the soul. On the other hand, Antisthenes is likely to have prompted Plato to specify the relationship between ideas and things in the definitory logic, since the proponent of the theory of oikeios logos refused to distinguish between the substance and its attributes, the differences and its opposites as well as the opposites of opposites.